Silencing Philosophers: Minteer and the Foundations of Anti-foundationalism. (1st November 1999) - Callicott, J.B.
Abstract : In 'No Experience Necessary: Foundationalism and the Retreat from Culture in Environmental Ethics', Ben A. Minteer forgivably misconstrues my critique of moral pluralism. Contrary to Minteer's representation: I do not accuse moral pluralists of 'moral promiscuity'; nor do I posit a 'master principle' to govern all human action respecting the environment; and although I offer conceptual foundations for environmental ethics, I do not claim that they rest on certain, a priori, and non-empirical intuitions. Rather, the conceptual foundations I offer for environmental ethics are largely scientific. Contrary to Minteer's representation: I do consider a multiplicity of contexts in which ethical actions are situated; and I do respectfully attend to and creatively engage a variety of cultural points of view, both western and nonwestern, in constructing environmental ethics. Anti-foundationalists, such as Minteer and Bryan G. Norton, ironically pose an insidious threat to democratic discussion and debate of environmental values, because they themselves posit, but do not frankly acknowledge, foundational beliefs.